2005
DOI: 10.1111/j.1471-0528.2005.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and current management of recurrent IVF treatment failure in the UK

Abstract: Objective To determine current practice in the management of recurrent in vitro fertilisation (IVF) treatment failure in licensed UK infertility centres. Design National postal questionnaire study and literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(79 citation statements)
references
References 74 publications
(74 reference statements)
0
73
0
6
Order By: Relevance
“…RIF may simply be defined as two or more continuous implantation failures (2); however, researchers now prefer to define RIF as the failure to maintain a clinical pregnancy following three cycles of ET (3,4). Several causes of RIF have been reported, including embryo, uterine and immunological factors, as well as thrombophilic conditions, however, the genetic mechanisms underlying RIF remain unclear (1).…”
Section: Introductionmentioning
confidence: 99%
“…RIF may simply be defined as two or more continuous implantation failures (2); however, researchers now prefer to define RIF as the failure to maintain a clinical pregnancy following three cycles of ET (3,4). Several causes of RIF have been reported, including embryo, uterine and immunological factors, as well as thrombophilic conditions, however, the genetic mechanisms underlying RIF remain unclear (1).…”
Section: Introductionmentioning
confidence: 99%
“…Forty women with a history of RIF after an ICSI-ET programme (defined in this study as a failure to achieve a pregnancy following 2 to 6 IVF cycles, in which more than 10 high-grade embryos were transferred to the uterus [39]. The control group comprised 131 women with at least one live birth after the transfer of fewer than 10 embryos.…”
Section: Patientsmentioning
confidence: 99%
“…A few years ago a new term -"repeated implantation failure" -was introduced (Margalioth et al, 2006;Tan et al, 2005). Recent years have shown that, despite the selection of obviously normal embryos for the transfer, only 20% of human embryos transferred in IVF cycles have been implanted in the uterus (International Committee for Monitoring Assisted Reproductive Technology (ICMART), 2002; Nyboe Andersen et al, 2009).…”
Section: Diminished Endometrial Receptivitymentioning
confidence: 99%
“…Margalioth et al (2006) concluded that detailed examination should be done after 3 unsuccessful IVF cycles. Thus, the main causes are the factors which diminish endometrial receptivity: anatomical defects in the uterus, chronic endometritis, non-correspondence between the endometrial thickness and the day of embryo transfer, combined gynecologic pathology (adenomyosis, uterine fibroid), somatic diseases (including autoimmune diseases), and thrombophilias (Margalioth et al, 2006;Tan et al, 2005).…”
Section: Diminished Endometrial Receptivitymentioning
confidence: 99%